Filtration in cohesive soils: mathematical model - Schaefer, Robert; Sędziwy, Stanisław (Computer Assisted Methods in Engineering and Science, 2023)
The paper discusses the physical basis of the process of filtration of water in a case of very low velocities and presents the mathematical model of the process, based on a new constitutive formula, The existence and uniqueness of a weak solution to the resulting nonhomogeneous initial boundary-value problem is then proven.